The Study of Iranian EFL Learnersâ Mental Lexicon through Word Association Tests - Shahram Halimi Passand, Farid Ghaemi (Journal of Educational, Health and Community Psychology, 2015)
Abstract This study intended to peek into Iranian EFL learnersâ metal lexicon through word association tests (WATs). 31 male and female EFL learners studying at Bonab and Marageh language institutes participated in this study. A WAT comprised of 8 English words adopted from Rouxâs (2013) word list administered to the participants. The results analyzed and interpreted according to both WA conventional classification and Fitzpatrickâs framework. Within conventional classification (syntagmatic, paradigmatic, and clang), the results confirmed the syntagmatic to paradigmatic change hypothesis (SâP) only between intermediate and upper-intermediate levels. The results also indicated that low intermediate learners besides other conventional factors, associate words based on phonological and orthographical relations. Within Fitzpatrickâs framework, the results indicated that learners generally associate words according to meaning and position across all proficiency levels. However, at low-intermediate level the rate of meaning-based association overwhelms position-based association. Form-based association and erratic association drew the least attention of the participants respectively. Finally, pedagogical implication of this study along with further research idea is discussed. Key words: conventional classification, Fitzpatrickâs framework, mental lexicon, word association test